Socialization of The Application of Language Skills for SD Teachers in Kecamatan Deket - Emalia Nova Sustyorini (Jurnal Mantik, 2020)
This study aims to describe: the socialization of the application of oral language skills for elementary school teachers and the role in improving written language skills for elementary school teachers in Deket District. This study used a qualitative research design. The main object of this research is the socialization of the application of language skills for elementary school teachers in Deket District. The location of this research is in the UPT Office of the Education Office, Deket District. The data in this study is a socialization of the application of oral language skills for elementary school teachers in Deket District and the role in improving written language skills for elementary school teachers in Deket District. The data collection techniques used were observation, interview, and note-taking techniques. The technique used is descriptive analysis techniques. The results of the research on the socialization of the application of skills in oral language for elementary school teachers in Deket sub-district are that elementary school teachers in Deket sub-district are an important means for their students in good and correct language through oral and written to be applied in their respective schools. Implementation of spoken language in everyday life, teachers admit that they are not able to speak or use spoken language with Indonesian in full because they tend to use the language that is widely used by the environment in which they live. The role in improving skills in written language for elementary school teachers in Deket sub-district is by means of the teacher applying a contextual approach in the form of modeling components that are expected to make students find it easier to write because they already have a picture that has been given by the teacher through an example, and it is hoped that students can develop ideas , their thoughts, and ideas so that learning objectives can be achieved